Analisis Pemborosan Waktu Produksi Pada Bagian Perakitan Rumah Boneka Menggunakan Pendekatan Lean - Tiara Tiara; Surya Perdana (Jurnal Optimasi Teknik Industri (JOTI), 2019)
CV. RB  which  is  the  object  of  this  research  is  a  manufacturing  company  producing  wood-based  doll houses. The purpose of this study is to evaluate waste and provide recommendations for improving the production  process  so  that  it  can  improve  the  efficiency  of  production  time  on  the  CV.  RB.  The  lean production system gives a good change to the company. In solving the problems that are being faced, the analysis carried out in this study is the analysis of NVA and NVAN using fishbone diagram data analysis techniques in this study in terms of NVA and NVAN. In the process of assembling the pattern there are 27 worker activities, starting from the ground floor assembly to the left to the installation of tile on the right. based on the VA, NVA and NVAN classification in the sanding process, it can be seen that there are 30 wastes in the NVA classification with a percentage of time of 19.2%, there are 18 wastes in the NVAN classification with a percentage time of 0.6%. Based on observations on the production floor there is a waste  of  time  in  the  process  of  assembling  the  pattern.  This  is  caused  by  several  factors,  namely: material,  human,  environment  and  machinery.  Some  waste  of  production  time  is  a  pattern  assembly process that results in long activities. waste contained in this assembly part is motion and waiting.